2016
DOI: 10.2215/cjn.06660615
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Geriatric Impairments in Patients Starting Dialysis: A Systematic Review

Abstract: Background and objectives With aging of the general population, patients who enter dialysis therapy will more frequently have geriatric impairments and a considerable comorbidity burden. The most vulnerable among these patients might benefit from conservative therapy. Whether assessment of geriatric impairments would contribute to the decision-making process of dialysis initiation is unknown.Design, setting, participants, & measurements A systematic Medline and Embase search was performed on December 1, 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 53 publications
1
40
0
2
Order By: Relevance
“…First, in studies focusing on one or more geriatric domains in patients on dialysis, a reduced functional performance, cognitive impairment, depression and immobility were all associated with negative outcomes, such as (early) mortality and hospitalizations [16]. Furthermore, frailty in patients with ESKD is associated with worse quality of life, irrespective of dialysis or MCM [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in studies focusing on one or more geriatric domains in patients on dialysis, a reduced functional performance, cognitive impairment, depression and immobility were all associated with negative outcomes, such as (early) mortality and hospitalizations [16]. Furthermore, frailty in patients with ESKD is associated with worse quality of life, irrespective of dialysis or MCM [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, elderly patients may benefit from dialysis, and age on itself is not a good selection criterion. Previous studies in the ESKD population showed that frailty is related to mortality, hospitalizations and falls [3,16]. Therefore, understanding the burden of geriatric impairments could provide an opportunity to direct treatment decisions and to start preventive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…31 Although these alternatives may not perform as well as CGA for identifying geriatric problems, some providers apply them to screen for patients who would benefit from CGA. 32…”
Section: Comorbidity Disability and Low Physical Activitymentioning
confidence: 99%
“…In addition to organ-system specific comorbid diseases, it is increasingly recognized that physical frailty, depression, and cognitive impairment are important contributing factors to the adverse clinical outcome of chronic kidney disease (CKD) and dialysis patients [4,5]. Frailty is defined as a clinically recognizable state of increased vulnerability resulting from aging-associated decline in reserve and function across multiple physiologic systems, such that the ability to cope with every day or acute stressors is comprised [6].…”
Section: Introductionmentioning
confidence: 99%